Muslim Kelas Menengah dan Proses Demokratisasi di Indonesia - Asep Saepudin Jahar (JURNAL INDO-ISLAMIKA, 2011)
This article discusses the role of Muslim middle class in making democratization in Indonesia. The democratization in Indonesia. The democratization in Indonesia has much indebted to the young Muslim’s contribution. This is started their efforts to enhance the sectors of economy, social, and education. Both social and educational sectors had become two main strategies to cultivate the democratization process. Surprisingly, the process of democratization had not happened within political parties, but in palces such as campuses and Islamic religious circles.